The comparison of language events between SMS and visual communication from the aspect of ethnography communication - Ab Rahman, Rosli; Musanif, Ahmad Mahmood; Abd Rahim, Normaliza; Zainon Hamzah, Zaitul Azma (Ubiquitous Learning: An International Journal, 2009)

(untitled)
This research seeks to find out the differences of events between Malay language SMS and virtual communication from the aspect of ethnography communication. The objectives of the research are to identify the communication component in the language event and the differences of SMS language event and the virtual communication from the aspect of ethnography communication. The methodology in this research involves library research and text analyses. The data were from the Malay language SMS from channel 15 Astro (private tv channel) and the virtual communication in the Portal Pendidikan Utusan. The instruments for analyzing the data are the transcription of Malay language SMS and the virtual communication. The data will be analyzed through analyzing the content of the texts. The theory used for this research is the Ethnography communication theory by Hymes (1972).